Thioredoxin Reductase Inhibition Elicits Nrf2-Mediated Responses in Clara Cells: Implications for Oxidant-Induced Lung Injury - Locy, Morgan L. (Mary Ann Liebert, Inc., 2012)
Aims: Pulmonary oxygen toxicity contributes to lung injury in newborn and adult humans. We previously reported that thioredoxin reductase (TrxR1) inhibition with aurothioglucose (ATG) attenuates hyperoxic lung injury in adult mice. The present studies tested the hypothesis that TrxR1 inhibition protects against the effects of hyperoxia via nuclear factor E2-related factor 2 (Nrf2)-dependent mechanisms. Results: Both pharmacologic and siRNA-mediated TrxR1 inhibition induced robust Nrf2 responses in murine-transformed Clara cells (mtCC). While TrxR1 inhibition did not alter the susceptibility of cells to the effects of hyperoxia, glutathione (GSH) depletion after TrxR1 inhibition markedly enhanced the hyperoxic susceptibility of cultured mtCCs. Finally, in vivo data revealed dose-dependent increases in the expression of the Nrf2 target gene NADPH:quinone oxidoreductase 1 (NQO1) in the lungs of ATG-treated adult mice. Innovation: TrxR1 inhibition activates Nrf2-dependent antioxidant responses in mtCCs in vitro and in adult murine lungs in vivo, providing a plausible mechanism for the protective effects of TrxR1 inhibition in vivo. Conclusion: GSH-dependent enzyme systems in mtCCs may be of greater importance for protection against hyperoxic exposure than are TrxR-dependent systems. The induction of Nrf2 activation via TrxR1 inhibition represents a novel therapeutic strategy that attenuates oxidant-mediated lung injury. Similar expression levels of TrxR1 in newborn and adult mouse or human lungs broaden the potential clinical applicability of the present findings to both neonatal and adult oxidant lung injury. Antioxid. Redox Signal. 17, 1407–1416.